RADIOSENSITIZING EFFECT OF PROTOPORPHYRIN IX WITH CARBON ION BEAM AGAINST MOUSE MAMMARY BREAST TUMOR CELL - Kaneko, T.; Tominaga, M.; Endo, H.; Yaju, K.; Kouzaki, R.; Yamada, H.; Nakanishi, I.; Matsumoto, K.; Uto, Y. (Journal of Advanced Manufacturing Technology (JAMT), 2016)
5-Aminolevulinic acid (ALA), a precursor of protoporphyrin IX (PpIX), has been utilized as a potent sensitizer for photodynamic therapy (PDT) of cancer through production of reactive oxygen species (ROS). ALA also has been proposed as a possible radiosensitizer with low linear energy transfer (LET) radiation because antitumor activity of low-LET radiation depends on ROS mainly. In this paper, we investigated the radiosensitizing activity of PpIX in carbon ion irradiation as a high LET radiation. PpIX was detected in an EMT6 mouse mammary breast tumor cells even at 24 h post treatment. The cytotoxicity of PpIX against EMT6 cells was IC50 = 48.0 μm. The combined treatment of 1.0 μm of PpIX with 2 Gy of carbon ion irradiation (290 MeV/nucleon, 85.1 keV/μm) showed a more potent antitumor activity than carbon ion irradiation alone. We demonstrated that PpIX showed a radiosensitizing effect with carbon ion beam against mouse mammary breast tumor cells.